2004
DOI: 10.1126/science.1095491
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Open Ocean Storage of CO 2 from Shelf Sea Pumping

Abstract: Seasonal field observations show that the North Sea, a Northern European shelf sea, is highly efficient in pumping carbon dioxide from the atmosphere to the North Atlantic Ocean. The bottom topography-controlled stratification separates production and respiration processes in the North Sea, causing a carbon dioxide increase in the subsurface layer that is ultimately exported to the North Atlantic Ocean. Globally extrapolated, the net uptake of carbon dioxide by coastal and marginal seas is about 20% of the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
491
10
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 491 publications
(526 citation statements)
references
References 21 publications
19
491
10
6
Order By: Relevance
“…Being nutrient-rich and with reduced stirring, the regions within the eddies can, thus, be favorable for biological production, as suggested by the increased fluorescence in the high-resolution Scanfish section (Figure 1f). This eddy transfer might then be an important complement to diapycnal mixing [Sharples et al, 2001] in sustaining the nutrient budget in stratified waters of the shelf seas and in the transfer of CO 2 [Thomas et al, 2004], as has been discussed for the open ocean [Williams and Follows, 2003]. …”
Section: Discussionmentioning
confidence: 99%
“…Being nutrient-rich and with reduced stirring, the regions within the eddies can, thus, be favorable for biological production, as suggested by the increased fluorescence in the high-resolution Scanfish section (Figure 1f). This eddy transfer might then be an important complement to diapycnal mixing [Sharples et al, 2001] in sustaining the nutrient budget in stratified waters of the shelf seas and in the transfer of CO 2 [Thomas et al, 2004], as has been discussed for the open ocean [Williams and Follows, 2003]. …”
Section: Discussionmentioning
confidence: 99%
“…About half of the approximately 115 pg of carbon fixed by autotrophs annually is taken in by marine organisms (Behrenfeld et al, 2001). It is estimated that about 30% of anthropogenic CO 2 emissions are absorbed into the oceans (Sabine et al, 2004) and the ocean margins have recently been shown to take up about 20% of this anthropogenic CO 2 (Thomas et al, 2004). Coastal seas, estuaries and river plumes are a fundamental part of the global carbon cycle because they link terrestrial, oceanic and atmospheric carbon reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…By fixing atmospheric carbon during photosynthesis, phytoplankton growth also plays an important role in regulating anthropogenic CO 2 concentrations in the atmosphere [e.g., Tsunogai et al, 1999;Thomas et al, 2004;Arrigo, 2005]. Nutrient and carbon cycles are therefore closely related and their understanding is crucial for modeling Earth's future climate.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this buffering effect, they are among the most physically and biogeochemically active regions of the oceans [Gattuso et al, 1998;Borges, 2005]. Although they occupy a small fraction of the ocean surface ( 7%), they sustain about 15-30% of the primary production and contribute to 20-50% of the carbon sequestration in the oceans [Wollast, 1998;Tsunogai et al, 1999;Thomas et al, 2004;Muller-Karger, 2005]. Large tidally induced turbulent mixing that typically characterizes coastal zones directly affects the magnitude of the oceanic carbon uptake, because primary production sustained by turbulent diapycnal nutrient fluxes is much more efficient for sequestrating carbon than the regenerated production resulting from nutrient recycling [Falkowski, 2000;Richardson et al, 2000;Sharples et al, 2001a;Allen et al, 2004;Rippeth, 2005;Rippeth et al, 2009].…”
Section: Introductionmentioning
confidence: 99%